DESIGN OF TELESCOPES OF THE CASSEGRAIN AND RITCHEYCHRETIEN TYPES - MALACARA HERNANDEZ, D (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1967)
The necessary equations for the design of a Cassegrain telescope are derived to first order. Also the conic constants are computed not only in the ordinary parabolic-hyperbolic system but also in the Ritchey-Chretien aplanatic system.
BOL OBS TONAN TACUB
Keywords: DESIGN, TELESCOPES, CASSEGRAIN, RITCHEY, CHRETIEN TYPES; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; TELESCOPIOS